Family and Peer Group Support Related to The Quality of Life of Thalassemic Adolescents in Outpatient Settings - Komariah, Elis; Sutini, Titin; Fauziah, Munaya; Sasmito, Priyo; Sumartini, Sri (International Journal of Public Health Excellence (IJPHE), 2024)
Thalassemia in Indonesia is dominated by teens. Thalassemic adolescents often experience psychosocial problems. The role of family and peer group support in the quality of life of thalassemic adolescents is still inconclusive. This study aim to determine the association between family and peer group support on the quality of life of thalassemic adolescents in one government hospital in Jakarta, Indonesia. An analytical observational study with a cross-sectional approach on β-thalassemia sufferers aged 12-18 years who came to the Children's Polyclinic and intervention room in November-December 2023. Family and peer group support was measured using the Social Support Scale, while quality of life was measured using the validated Generic Pediatric Quality of Life Inventory Version 4.0 (PedsQL). The data obtained were analyzed using Chi-Square and logistic regression tests. Forty-three patients were involved in this study. The average age of respondents was 14.4 years (range 13.8 – 15.1), the average time of diagnosis was 9.49 years (range 8.0 – 11.0), the average hemoglobin (Hb) level was 9.2 gr/dl (range 8.7 – 9.6 gr/dl). The majority of respondents were male (65.1%), had low education (60.5%), and had a good adherence to iron chelation therapy (100%). The association between family and peer group support on quality of life obtained a p-value of 0.014 and 0.006 with an Odd Ratio (OR) of 4.976 and 7.333 respectively. There is a significant relationship between family and peer group support on the quality of life of thalassemic adolescents. It is recommended for health workers to improve the quality of life of thalassemic adolescents with a family and peer group support approach. Further studies are needed to confirm the results of this study.